Spray dried human and chimpanzee adenoviral-vectored vaccines are thermally stable and immunogenic in vivo. Issue 22 (19th May 2017) - Afkhami, Sam; LeClair, Daniel A.; Haddadi, Siamak; Lai, Rocky; Toniolo, Steven P.; Ertl, Hildegund C.; Cranston, Emily D.; Thompson, Michael R.; Xing, Zhou
Highlights: Human and chimpanzee adenoviral-vectored vaccines spray dried in a sugar matrix. Spray dried vaccine powders demonstrate thermostability and in vivo efficacy. Spray dried vaccine powders when stored, cold chain-free, are stable up to 90 days. Abstract: Cold chain-free vaccine technologies are needed to ensure effective vaccine delivery and coverage, particularly in resource-poor countries. However, the immunogenicity and thermostability of spray dried live viral vector-based vaccines such as recombinant adenoviral-vectored vaccines remain to be investigated. To address this issue, we have spray dried human adenoviral (AdHu5)- and chimpanzee adenoviral (AdCh68)-vectored tuberculosis vaccines in a mannitol and dextran matrix. Spray dried powders containing these two vaccines display the morphologic and chemical properties desired for long-term thermostability and vaccination. Upon reconstitution, they effectively transfected the cells in vitro with relatively small losses in viral infectivity related to the spray drying process. Following in vivo vaccination, AdHu5- and AdCh68-vectored vaccines were as immunogenic as the conventional fresh, cryopreserved liquid vaccine samples. Of importance, even after cold chain-free storage, at ambient temperatures and relatively low humidity for 30 and 90 days, the vaccines retained their in vivo immunogenicity, while the liquid vaccine samples stored under the same conditions lost their immune-activating capability almost entirely. Our results support further development of our spray drying technologies for generating thermally stable adenoviral-vectored and other viral-vectored vaccines.